REDESAIN LINGKUNGAN SEKOLAH DARUSSALAM PANONGAN SEBAGAI RUANG BELAJAR TERINTEGRASI BERKELANJUTAN MELALUI PENDEKATAN PARTISIPATIF [REDESIGNING THE DARUSSALAM PANONGAN SCHOOL ENVIRONMENT AS A SUSTAINABLE INTEGRATED LEARNING SPACE THROUGH PARTICIPATIVE APPROACHES] - Gregorius Anugerah Gegana; Emanuel Agung Wicaksono (Jurnal Sinergitas PKM & CSR, 2020)
The school environment is a powerful tool to stimulate and enhance creativity, concentration, motivation, and understanding for students. Darussalam School, Panongan has a GSM program which is Fun School Movement. This GSM program encourages students to create a friendly, safe and comfortable school ecosystem. With a total of about 700 students ranging from PAUD to SMK (Vocation Senior High School), this school has the potential to produce students who have sensitivity and responsibility for their environment. Community Service Activities (PkM) is directed to design a Darussalam School-Build environment that is able to create sustainable schools based on the GSM program. In the process, it is hoped that the design is not just the result of the thaught of the architech but also is the result of the formulation of the needs and desires of the user be it teachers, students, parents, and other stakeholders through a participatory design approach that emphasizes community joint planning, with the aim of increasing ties high and sustainable social and participation. Through the implementation of Darussalam school design, it is expected to produce a school environment that is able to stimulate the students to be sensitive to envoronmental problems. Academically, this participatory design process is a good learning process because the approach is different from the conventional architectural design process, so the resulting design products can be relevant to the needs and desires of school users. Although this design has not yet been fully developed, this participatory process encourages teachers and students to be more sensitive in caring for their environment through collaboration spirit.Bahasa Indonesia Abstrak: Lingkungan sekolah merupakan alat yang ampuh untuk menstimulasi dan meningkatkan kreativitas, konsentrasi, motivasi, dan pengertian bagi para siswanya. Sekolah Darussalam, Panongan memiliki program GSM yakni Gerakan Sekolah Menyenangkan. Program GSM ini mendorong agar siswa dapat mewujudkan ekosistem sekolah yang ramah, aman, dan nyaman. Dengan jumlah peserta didik sekitar 700 siswa mulai dari PAUD sampai dengan SMK, sekolah ini berpotensi mencetak siswa yang memiliki kepekaan dan tanggung jawab terhadap lingkungannya. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini diarahkan untuk merancang lingkungan binaan sekolah Darussalam yang mampu mewujudkan sekolah berkelanjutan berlandaskan program GSM. Dalam prosesnya, diharapkan desain bukan semata sekedar hasil olah pikir dari arsitek namun juga merupakan hasil formulasi dari kebutuhan dan keinginan pengguna baik itu guru, siswa, orang tua, dan stakeholder lainnya melalui pendekatan desain partisipatif yang menekankan perencanaan bersama komunitas, dengan tujuan untuk meningkatkan ikatan sosial dan partisipasi yang tinggi dan berkelanjutan. Melalui pelaksanaan perancangan sekolah Darussalam ini, diharapkan dapat menghasilkan lingkungan sekolah yang mampu menstimulus siswanya untuk peka terhadap permasalahan lingkungan. Secara akademik, proses desain partisipatif ini menjadi sebuah pembelajaran yang baik dikarenakan pendekatannya yang berbeda dari proses desain arsitektur yang konvensional, sehingga produk desain yang dihasilkan dapat relevan dengan kebutuhan dan keinginan pengguna sekolah. Meskipun desain ini belum sepenuhnya terbangun, namun proses yang dilalui secara partisipatif ini mendorong guru dan siswa untuk lebih peka merawat lingkungannya melalui semangat kolaborasi.